Accelerating machine learning at the edge with approximate computing on FPGAs - León-Vega, Luis Gerardo (2022)
Performing inference of complex machine learning (ML) algorithms at the edge is becoming important to unlink the system functionality from the cloud. However, the ML models increase complexity faster than the available hardware resources. This research aims to accelerate machine learning by offloading the computation to low-end FPGAs and using approximate computing techniques to optimise resource usage, taking advantage of the inaccurate nature of machine learning models. In this paper, we propose a generic matrix multiply-add processing element design, parameterised in datatype, matrix size, and data width. We evaluate the resource consumption and error behaviour while varying the matrix size and the data width given a fixed-point data type. We determine that the error scales with the matrix size, but it can be compensated by increasing the data width, posing a trade-off between data width and matrix size with respect to the error.